Challenges Arising from Article 22(2) of Ministerial Regulation ATR/BPN No. 6/2018 on Complete Systematic Land Registration (PTSL) Pertaining to Insufficient or Missing Evidence of Community Land Ownership - Fida Nabilah Taufiq; Mohammad Hamidi Masykur; Supriyadi Supriyadi (Universitas Negeri Semarang, 2023)
The Complete Systematic Land Registration (PTSL) program's successful implementation hinges on satisfying the physical and juridical data requirements for individual land plots owned by a single person. However, our research highlights disparities between juridical and physical data for specific land plots. Moreover, a lack of community awareness regarding the crucial role of land data collection presents significant challenges in the field. A notable obstacle, as outlined in Article 22(2) of the Regulation of the Minister of Agrarian and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia No. 6 of 2018, pertains to individuals applying for land registration through the PTSL Program without fulfilling complete requirements or providing proof of land ownership. This non-compliance poses a potential catalyst for disputes during the PTSL land registration process. As of early 2017, Indonesia harbored 126,000,000 land parcels, with only 51,000,000 certified and 79,000,000 awaiting official registration, earmarked for acceleration through PTSL. Our focus on Malang Regency in East Java, spanning an expansive 3,534.86 km² or 353,486 ha, reveals its active participation in the PTSL program. Notably, the region faces a substantial PTSL quota of 55,000 land parcels in 2023, distributed across 19 villages in 5 sub-districts, marking the highest quota in East Java Province. The research also underscores the pressing need for enhanced community awareness and compliance with PTSL requirements, particularly focusing on the potential disputes arising from inadequate documentation during the land registration process.